FORMATION OF PROFESSIONAL QUALITIES OF THE FUTURE STUDENT LEADER MUSICAL AND INSTRUMENTAL BANDS (Pedagogy of Higher and Secondary Education, 2022)
The author of the article develop the complex of professional qualities of future leader of student's orchestras and instrumental bands. His constituents - personality qualities, capabilities , knowledges, skills, abilities are analysedю
Keywords: 1